A study on selecting optimum flash and evaporation temperatures for four geothermal power generation systems under different geofluid's conditions. (December 2017) - Zhao, Yangyang; Lu, Xinli; Zhu, Jialing; Zhang, Wei; Hu, Kaiyong; Xin, Guanglei; Jiang, Feng; Qin, Zhen
Abstract: In this study, the optimum flash and evaporation temperatures have been selected for the following four geothermal power generation systems: single-flash system (SF), double-flash system (DF), flash-organic Rankine cycle system (FORC), and double-flash-organic Rankine cycle system (DFORC). Optimization is based on the maximum net power output of each system, with the pump and fan consumptions being taken into account. Under the given geofluid's condition (temperature= 170ºC; dryness= 0.2), the optimum flash temperature of SF, the optimum 2 nd -stage flash temperature of DF, the optimum evaporation temperatures of FORC and DFORC are found to be 150ºC, 100ºC, 100ºC, and 70ºC, respectively. More scenarios have been analyzed for geofluid's temperatures ranging from 80ºC-260ºC and geofluid's dryness values of 0, 0.2, and 0.4 respectively. The result shows that the optimum 2 nd -stage flash temperature of DF is close to the optimum evaporation temperature of FORC under the same geofluid's condition, especially when the geofluid's temperature is below 170ºC and the dryness is below 0.2.